Provenance of the Neogene sediments from the Solimões Formation (Solimões and Acre Basins), Brazil. (August 2019) - Horbe, Adriana Maria Coimbra; Roddaz, Martin; Gomes, Luciane Batista; Castro, Rodrigo Tokuta; Dantas, Elton Luiz; do Carmo, Dermeval A.
Abstract: This study investigates the provenance of middle-late Miocene to Pliocene sediments of the Solimões Formation, in western Brazilian Amazonia, to complement the geological history and fill the gap left by similar studies on other foreland basin deposits and in the Amazonian fan. The major and trace element concentrations and Sr–Nd isotopic compositions of sixteen samples from the 1AS 33AM borehole and fifteen samples from two sections outcropping in the Acre and Yaco rivers were measured for determining their provenance. Additionally, the heavy mineral assemblages of the sixteen borehole samples were determined to complement the geochemical provenance interpretation of the borehole sediments. The Nd isotopic compositions of the Solimões Formation indicate that the Andes was the principal source of these Neogene sediments. While the middle-late Miocene borehole sediments are dominated by stable assemblage (zircon, tourmaline, and rutile) and less radiogenic Nd isotopic values, the Pliocene borehole sediments have a larger amount of more unstable mineral assemblages (epidote, pyroxene, and amphibole) and more radiogenic Nd isotopic values. These mineral and isotopic differences between the middle-late Miocene and Pliocene sediments are interpreted to reflect a change in provenance with increasing contribution of metamorphic and young Nd radiogenic source in the Pliocene most probably related to the late Miocene uplift of the Peruvian Eastern Cordillera. These changes that precede the paleoenvironmental changes highlighted by the palynological study of Leite et al. (2017) suggest that the Andean tectonics drove the middle to late Miocene paleoenvironmental changes of the Amazon basin from the Pebas mega-wetland to the more fluvial Acre phase. Highlights: Nd isotopic ratios and heavy mineral indicate an Andean source for Neogene sediments of the Solimões Formation. Metamorphic heavy minerals and Nd isotopic ratios suggest contribution from the Peruvian Eastern Cordillera for Pliocene sediments. Middle to late Miocene paleoenvironmental changes in the Acre basin driven by uplift of Eastern Cordillera and Andean Building.